Development and Applications Of Photoflash-Pvdf Technique in Thermal Diffusitivity Measurement at Low Temperatures - Haydari, Mehdi (2004)
The photoflash technique is developed and used for measuring thermal diffusivity of various types of material, at temperature range from -77K to ambient temperature. It uses a cheap and simple camera flash and polyvinlidene difluoride (PVDF) film as signal generating source and detector, respectively. The theoretical signal was derived based on the square pulse approximation of the camera flash that replaced Dirac-6 function approximation employed in other studies. Comparative studies on these two different approximations have been performed on SiCIB4C composites. Although the camera flash temporal shape is closer to square pulse, Dirac-6 function approximation is still valid for the limited case of PVDF signal that is significantly longer than camera flash pulse duration. The square wave approximation model was further used in determining the thermal diffusivity of superconductors, semiconductors, magnetoresistances, carbon nanotubes, ceramics, composites, polymers and porous samples. The thermal diffusivity for SiC/B4C composites and Sic doped with A1 decreased with increasing temperature. This suggests that thermal diffusivity is basically influenced by phonon interaction within lattice that determines the phonon mean free path. In case of superconducting materials, thermal diffusivity measurements were carried for BSCCO, doped with Samarium (Sm) at Bi, Sr and Cu sites and sintered for 24,48 and 100hrs respectively. The results were explained in terms of electronphonon and phonon-lattice interactions in association with the sample grain size. The magneto-resistive of LCMO doped with Er at La site was also studied in this study. Thermal diffusivity measurements revealed that the transition from metallic to insulator and from insulator to semiconductor behavior in the materials, were closely matched to the results obtained from electrical resistivity measurement of other researchers. The thermal diffusivity of carbon nanotubes (CNTs) decreased when the temperature was increased from low to room temperature. Besides, there were also double slope phenomena in the way the thermal diffusivity changed with composition of CNT in the range of temperature covered in the measurement. In the case of polymers of Emeraldine Base (EB) and Emeraldine Salt (ES), the thermal diffusivity changed with temperature as in other insulating materials. Finally, the effect of porosity on thermal diffusivity was studied using Nickel Copper Zinc Ferrite samples. The thermal diffusivity decreased with increasing porosity of the sample. The results also showed that porosity has a greater effect on thermal conductivity of the material than its thermal capacity.